Textbook of MEDICAL PHYSIOLOGY - Guyton, Arthur C., Professor; Wonsiewicz, Martin J. (Philadelphia : W. B. Saunders Company, 1991)
This textbook offers current authoritative coverage that is easy to read and understand. It provides coverage of molecular and cellular physiology, long-term arterial pressure regulation and hypertension, the neurophysiology of vision, the body's resistance to infection, and physiology from a quantitative perspective. The new edition integrates the latest information throughout the text, and helps students relate physiology to other aspects of medicine and analyze problems
Includes bibliographical references and index
Keywords: Human physiology; Physiology, Pathological